Prevalence of oral lesions in pan vendor - Prakash Gadodia; Vinay Hazare; Sindhu Ganvir; Sunil Sahuji (Wolters Kluwer Medknow Publications, 2011)
Background: Being a portal of entry to various smoking and smokeless tobacco products, oral cavity is prone to deleterious effects. Present study consist of epidemiological survey to elucidate oral lesions in pan vendors. Aims and objectives: To detect oral lesions in pan vendors and compare it with controls. To detect habit pattern and prevalence of OSMF and other lesions in pan vendors as compared to controls- To identify, recognize and evaluate the possible etiology for OSMF, encompassing various chewing and smoking habits. Materials and methods: Study population consist of 170 pan vendors with age ranging from 15 to 55 years and equal number of sex matched controls selected randomly. Results: Prevalence of oral lesions in pan vendors is statistically significantly higher as compared to controls. The habit of arecanut chewing in various forms was present in all cases. The habit of smoking and smokeless tobacco products was present in all cases. Conclusion: Pan vendors are at higher risk for oral lesions than controls. There is increase in relative risk with increase in duration and frequency of habit.